1995
DOI: 10.1111/j.1467-9817.1995.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

The metacognitive reading strategies of five early readers

Abstract: The purpose of this study was to examine the metacognitive reading strategies of five children, four to six years of age, who were reading fluently prior to formal instruction in grade one. Fluency was judged on whether the children could conduct meaningful reading (Smith, 1988) with relative smoothness (Duffy and Roehler, 1989). Methods of this case study included semi-structured interviews, role playing, observations and informal miscue analyses of oral reading. The children's personal characteristics and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…The results of this study support the research that indicates there is a developmental trend to children's metacognitive behaviors during book-reading activities (Brenna, 1995;Siegler, 1996;Wellman, 2002) as well as builds on this research base. In examining the data across grades, the students' responses fell within similar categories.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study support the research that indicates there is a developmental trend to children's metacognitive behaviors during book-reading activities (Brenna, 1995;Siegler, 1996;Wellman, 2002) as well as builds on this research base. In examining the data across grades, the students' responses fell within similar categories.…”
Section: Discussionsupporting
confidence: 86%
“…Cox's study revealed the need for more inquiry about the impact of children's developmental level (those who lack early reading skills and those who do not) on young children's strategy use and decision making while reading. Brenna (1995) examined five children's (4-6-year-olds) use of strategies. These children were reading fluently prior to first grade.…”
Section: Young Children's Metacognitive Strategiesmentioning
confidence: 99%
“…Retrospection provided more information on metacognitive knowledge while observing the children during intervention lessons provided more data on self-management. Brenna (1995) also found in a study of the metacognitive strategies of early readers that a variety of techniques were needed when studying young children. Only by using multiple measures of metacognition will an accurate picture of any child's metacognition be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McEwan (2004) described deliberative cognitive strategies-behaviors and thoughts-that make reading and learning more efficient. We know that students use multiple strategies for reading, which may differ over age, reading level, and context (Baker, 2005;Brenna, 1995;Brown, Pressley, Van Meter, & Schuder, 1996;Gersten, Fuchs, Williams, & Baker, 2001;Kragler & Martin, 2009;Paris & Flukes, 2005). In this article, text-level strategies (rather than word-level strategies) were our main focus.…”
mentioning
confidence: 99%